Drug Science and British Drug Policy: Critical Analysis of the Misuse of Drugs Act 1971 - Crome, Ilana B. (Waterside Press, 2022)
A thorough examination of the 1971 Act which challenges long outmoded ideas. Demonstrating political and media distortions the book calls for fresh thinking and urgent reform. Drug Science and British Drug Policy is first-rate, in-depth and highly informed.